Effects of radio-frequency fields on bacterial cell membranes and nematode temperature-sensitive mutants - Gul Guven, Reyhan; Guven, Kemal; Dawe, Adam; Worthington, John; Harvell, Christopher; Popple, Amy; Smith, Tim; Smith, Brette; de Pomerai, David I. (Elsevier, 2006)
Membrane-related bioeffects have been reported in response to both radio-frequency (RF) and extremely low-frequency (ELF) electromagnetic fields (EMFs), particularly in neural cells. We have tested whether RF fields might cause inner membrane leakage in ML35 E. coli cells, which express β-galactosidase (lacZ) constitutively, but lack the lacY permease required for substrate entry. The activity of lacZ (indicating substrate leakage through the inner cell membrane) was increased only slightly by RF exposure (1 GHz, 0.5 W) over 45 min. Since lacZ activity showed no further increase with a longer exposure time of 90 min, this suggests that membrane permeability per se is not significantly affected by RF fields, and that slight heating (≤ 0.1°C) could account for this small difference. Temperature-sensitive (ts) mutants of the nematode, Caenorhabditis elegans, are wild-type at 15°C but develop the mutant phenotype at 25°C; an intermediate temperature of 21°C results in a reproducible mixture of both phenotypes. For two ts mutants affecting transmembrane receptors (TRA-2 and GLP-1), RF exposure for 24 h during the thermocritical phase strongly shifts the phenotype mix at 21°C towards the mutant end of the spectrum. For ts mutants affecting nuclear proteins, such phenotype shifts appear smaller (PHA-1) or non-significant (LIN-39), apparently confirming suggestions that RF power is dissipated mainly in the plasma membrane of cells. However, these phenotype shifts are no longer seen when microwave treatment is applied at 21°C in a modified exposure apparatus that minimises the temperature difference between sham and exposed conditions. Like other biological effects attributed to microwaves in the C. elegans system, phenotype shifts in ts mutants appear to be an artefact caused by very slight heating.